The hate next door : undercover within the new face of white supremacy - Browning, Matson; Browning, Tawni (Sourcebooks, 2023)
"In THE HATE NEXT DOOR, retired police officer and founder of the Skinhead Intelligence Network, Matson Browning, tells the incendiary story of his time undercover in hate groups across Arizona. He also traces the rise and fall of J.T. Ready, a white supremacist, militia member, and later, elected official and murderer. Through it all, Browning illuminates the sociopolitical factors shaping the modern white supremacy movement, and exposes the varied profiles of its members. Between the braided narratives of Ready's rise to power and Browning's own experiences deep undercover, THE HATE NEXT DOOR, gives readers unparalleled insight into the dark and complicated workings of modern white supremacy, teaching readers to recognize the warning signs and empowering them to fight back"--